Komik Digital Sebagai Sarana Pelestarian Sastra Dan Budaya Lokal - Anita Candra Dewi (Prodi PGSD Unsultra, 2024)
Digital comics have developed as a modern literacy medium that is not only entertaining but also contributes to the preservation of local literature and culture. This study explores the role of digital comics in introducing and preserving local wisdom through innovative visual and narrative approaches. The results of the literature review indicate that digital comics are able to adapt folklore, legends, and cultural values ​​into a format that is more attractive to the younger generation. In addition, interactive features in digital comics allow readers to better understand and appreciate the cultural context being raised. The advantages of accessibility and visual appeal also contribute to expanding the reach of local literature to a wider audience. Thus, digital comics can be an effective means of maintaining the existence of local literature and culture amidst technological developments and globalization, ensuring that cultural heritage remains relevant and can be enjoyed across generations.